2020
DOI: 10.1177/0018720820946896
|View full text |Cite
|
Sign up to set email alerts
|

How Human Factors Can Help Preserve Democracy in the Age of Pandemics

Abstract: Objective To describe user-centered voting systems that would support the safe conduct of voting in a pandemic environment. Background The COVID-19 pandemic has complicated our democratic processes. Voters and poll workers feel threatened by the potential dangers of voting in business-as-usual polling stations. Indeed, significant problems were encountered in the recent 2020 primary elections in Wisconsin, where the National Guard had to be mobilized because so few poll workers reported to work, and more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The public policies made in response to the COVID-19 pandemic have complicated social life and democratic processes ( Kortum et al., 2020 ). In fact, these political actions are considered a serious threat to democracy, as governments may try to limit democratic rules under the cover of pandemic management.…”
Section: Introductionmentioning
confidence: 99%
“…The public policies made in response to the COVID-19 pandemic have complicated social life and democratic processes ( Kortum et al., 2020 ). In fact, these political actions are considered a serious threat to democracy, as governments may try to limit democratic rules under the cover of pandemic management.…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggest that members of polling stations were not at increased risk of infection. This finding is important for future decisions of holding elections elsewhere, as in some other places a percentage of polling stations were closed due to lack of available poll members as they feared to be infected by SARS-CoV-2 [7].…”
Section: Discussionmentioning
confidence: 99%
“…In the lead up to the 2020 election, many Americans were fearful of the coronavirus, with over 70% concerned they or their family would contract Covid (Kamisar & Holzberg, 2020). At the same time, they supported Covid safety measures in and outside of the voting booth (Douglas & Zilis, 2020; Funk & Tyson, 2021; Kortum et al, 2020; Kousser et al, 2021), believed they were effective (Pew, 2020a), and reported they would feel safer voting in-person if their local polling place was properly outfitted to protect voters from Covid-19 (Kousser et al, 2021). Given these patterns in public support for and trust in Covid safety measures, this study expects that in-person voters who cast their ballot in polling places with Covid safety features will be more confident they are safe from the Covid pandemic.…”
Section: Covid-19 Policies and Evaluations Of Election Administrationmentioning
confidence: 97%